2022
DOI: 10.1088/0256-307x/39/12/127402
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Two-Dimensional Nature of High-T c Superconductivity in Iron-Based (Li,Fe)OHFeSe

Abstract: The intercalated iron selenide (Li,Fe)OHFeSe has a strongly layered structure analogous to the quasi two-dimensional (2D) bismuth cuprate superconductors, and exhibits both high-temperature (T c) and topological superconductivity. However, the issue of its superconductivity dimensionality has not yet been fully investigated so far. Here we report that the quasi-2D superconductivity features, including the high anisotropy γ = 151 and the associated quasi-2D vortices, are also revealed for (Li,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…The relationship to vortex phases in more 2D cuprates, such as BSCCO, is focus of recent investigations regarding transport anisotropy. Indeed, in a recent publication [51], Li et al showed that (Li,Fe)OHFeSe is equally anisotropic as BSCCO with H c2 anisotropies around 150 close to T c with 2D-like angular dependence of H c2 , which allowed completing and explaining the vortex phase diagram within the vortex glass region. With the help of relaxation measurements and J c maxima (determined via magnetization), the transition between a 3D vortex solid and quasi-2D pancake vortices was determined.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…The relationship to vortex phases in more 2D cuprates, such as BSCCO, is focus of recent investigations regarding transport anisotropy. Indeed, in a recent publication [51], Li et al showed that (Li,Fe)OHFeSe is equally anisotropic as BSCCO with H c2 anisotropies around 150 close to T c with 2D-like angular dependence of H c2 , which allowed completing and explaining the vortex phase diagram within the vortex glass region. With the help of relaxation measurements and J c maxima (determined via magnetization), the transition between a 3D vortex solid and quasi-2D pancake vortices was determined.…”
Section: Physical Propertiesmentioning
confidence: 99%